Evaluation of bone marrow aspirate in paediatric patients with pancytopenia: a 2 years study - Baig, Mirza Asif (International Journal of Research in Medical Sciences, 2017)
Background: Pancytopenia is an important clinico-hematological entity, characterized by a triad of Anemia, leucopenia and thrombocytopenia. It’s not a disease entity itself but a manifestation of many serious and life-threatening diseases. The criteria for defining Pancytopenia is Hemoglobin (HGB) <9 g/dL; total leukocyte count (TLC) <4,000 / µL or absolute neutrophil count (ANC) is < 1.5x 109/ L; platelet count, <100 x 109/ L. The main objective of this study is to classify pancytopenic cases on etiological basis. Methods: A total of 750 bone marrow smears of pancytopenic patients were studied. Results: It comprised of 72 % boys & 28 % girls with the highest number of cases < 5 years of age (64%).The maximum number of cases were of ALL and Aplastic anemias. Conclusions: CBC, clinical findings and PBS provides valuable information in the workup of pancytopenic patients and help in planning additional investigations on bone marrow samples. Bone marrow evaluation is a valuable diagnostic procedure which may confirm the diagnosis of suspected cytopenias. So the take home message is a) pediatric leukemias unlike adults, usually presents with pancytopenia b) CBC+ PBS + BMA with flow cytometry can help in diagnosing majority of pancytopenias.